2011
DOI: 10.1103/physreva.84.053811
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of the dielectric permittivity of dense and cold atomic gases

Abstract: On the basis of general theoretical results developed previously in [JETP 112, 246 (2011)], we analyze the atomic polarization created by weak monochromatic light in an optically thick, dense, and cold atomic ensemble. We show that the amplitude of the polarization averaged over a uniform random atomic distribution decreases exponentially beyond the boundary regions. The phase of this polarization increases linearly with increasing penetration into the medium. On these grounds, we determine numerically the wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 53 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…This condition is thus similar to the so-called Ioffe-Regel criterion of Anderson localization [3]. In this density regime, it has been shown that the effective dielectric permittivity can be negative [16]. The decrease of the elastic mean free path due to recurrent scattering has been discussed in Refs.…”
mentioning
confidence: 62%
“…This condition is thus similar to the so-called Ioffe-Regel criterion of Anderson localization [3]. In this density regime, it has been shown that the effective dielectric permittivity can be negative [16]. The decrease of the elastic mean free path due to recurrent scattering has been discussed in Refs.…”
mentioning
confidence: 62%
“…The theoretical approach used has been described elsewhere [43,61,64,65,67], and for the convenience of the reader is summarized in the Appendix. To have possibilities of contrasting the results of the theory with experiments, we choose the density of our motionless four-level atoms in such a way that photons will have the same mean free path as in the 87 Rb samples.…”
Section: B Detuning Dependencementioning
confidence: 99%
“…A natural place to study strong dipole-dipole interactions is in cold atom systems, where a high level of control of the interaction strength and atom spacing is possible. Much work has already been carried out on theoretical understanding of light scattering through cold atom gases [5][6][7][8][9][10] with some of these effects being realised experimentally [11,12]. Most work focuses on the low light intensity limit, where interactions between excitations is negligible and the full quantum model simplifies to a problem of classical scatterers.…”
Section: Introductionmentioning
confidence: 99%